ASUMSI RASIONALITAS DALAM EKONOMI ISLAM - Azis, Fahnur; Arifin, Ahmad; Albahi, Muhammad (Politeknik Bisnis Indonesia, 2024)
This research examines the concept of rationality in Islamic economics as an alternative paradigm to the understanding of conventional economic rationality. This critical study shows that rationality in Islamic economics does not simply maximize material utility, but includes more comprehensive spiritual, moral and social considerations. Through a qualitative-normative approach, the study explores a conceptual framework that integrates ethics and spirituality in economic decision-making.